2019
DOI: 10.1093/iwc/iwz009
|View full text |Cite
|
Sign up to set email alerts
|

How Different Personalities Benefit From Gamification

Abstract: Several studies indicate the benefit of mapping gamification elements to personality. However, this mapping requires a strong understanding of the relationship between gamification elements and personality. The existing research that has tried to address this relationship is based on a self-report questionnaire that is obtained from only those learners who complete the entire study. Unfortunately, a bias may result from first forcing learners to complete an entire study and then ignoring learners who drop out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
(55 reference statements)
1
12
0
1
Order By: Relevance
“…Contrarily, students with high neuroticism have negative correlation with all of the four learning styles. This coincides with a study by [14] stating that gamification elements have a negative effect on the motivation for highly neurotic learners as they considered the elements to be "silly" and "toylike." These students have low motivation to learn in general as they tend to suffer from anxiety and moodiness.…”
Section: The Hybrid Learning Modelsupporting
confidence: 87%
See 2 more Smart Citations
“…Contrarily, students with high neuroticism have negative correlation with all of the four learning styles. This coincides with a study by [14] stating that gamification elements have a negative effect on the motivation for highly neurotic learners as they considered the elements to be "silly" and "toylike." These students have low motivation to learn in general as they tend to suffer from anxiety and moodiness.…”
Section: The Hybrid Learning Modelsupporting
confidence: 87%
“…Researchers [14] measured the drop-out rate and motivation based on the Big Five personality model for high school students learning Microsoft Excel online. The study revealed that for some personality types, the gamification elements helped in increasing motivation while for other personalities types, the gamification elements did not provide much benefit.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies show that certain personality traits are associated with specific coping behaviors [ 58 , 59 ] and app usage behaviors [ 60 , 61 ], as well as the response to gamification elements [ 62 ]. Individuals with personality factors such as high neuroticism, for example, show more vulnerability toward high stress values and problem coping strategies such as wishful thinking, withdrawal, and emotion-focused coping [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Entre los diferentes resultados obtenidos de ciertas investigaciones recientes, se describen los efectos positivos sobre el aprendizaje y el alumnado en general, como pueden ser el incremento de la motivación (Hassan, Dias & Hamari, 2019), el desarrollo de la personalidad (Ghaban & Hendley, 2019) y del pensamiento reflexivo (Peña, Fernández, Kirillof & Tovar, 2011), el interés por el aprendizaje y la participación activa (Lee and Hammer, 2011;Measles & Abu-Dawood, 2015;Rouse, 2013) y la adquisición de aprendizajes curriculares (Gros, 2008); los hábitos de aprendizaje y las habilidades para la resolución de problemas (Harrold, 2015), la mejora de la socialización (Montilla, 2015;Park & Kim, 2019), el trabajo cooperativo y la comunicación entre iguales (Roemer & Rundle, 2018;Sánchez, Alfageme & Serrano, 2010), el desarrollo de reflejos, psicomotricidad (Rodríguez & Martín), iniciativa y autonomía e identidad en niños y jóvenes (Aguilar & Aguilar, 2018), la participación de las familias en el proceso educativo (Vázquez & López, 2016), o el de adquirir competencias tecnológicas: cognitivas, metodológicas y organizativas (Borrás, 2018;Fernández, Rodríguez & Verdeja, 2017).…”
Section: Introductionunclassified